A new approach to organisational excellence for small and medium enterprises: the QOE-SME model - Correia, Fábio Daniel (2021)
This paper presents the development of a new organisational excellence model specifically for use by small and medium-sized enterprises (SME). A literature review was undertaken examining the current state of business excellence models, and their content and use worldwide, including the identification of the key concepts that drive their development and implementation. In this paper, we do present a framework that was validated by a worldwide experts' panel in Organisational Excellence, taking into consideration the unique characteristics of SME and its industry contexts. It is hoped that the model will allow these enterprises to strive towards organisational excellence using a framework that better fits to their context and needs.